Modeling Carrying Capability of Agricultural Land with Spatial Autoregressive Model (SAR) in Batu City - Meilinda Trisilia; Henny Pramoedyo; Suci Astutik (Natural B, Journal of Health and Environmental Sciences, 2014)
Increasing population growth can lead to the availability of agricultural land becomes smaller, it causes an imbalance of farmers population in a region with an area of agricultural land there, so the population pressure on agricultural land will be greater so that the region no longer can meet the needs of food population. If this happends continue then it is not impossible that the production has not proportional to the needs of existing population, and resulted in the carrying capacity of agricultural land will be smaller. So the analysis of the carrying capacity of agricultural land needs to be done to determine the ability of the land to provide food for the population needs in a given area. Carrying capacity of agricultural land is a function of several spatial variables may give effect in spatial linkages. The model can explain the relationship between variables that have a spatial relationship is called spatial regression models. One of the effective spatial regression models to estimate the effects of data that has a spatial dependency in the response variable is Spatial Autoregressive (SAR) model. Agricultural land supporting food is a phenomenon of spatial autocorrelation. Based on observations made at the carrying capacity of agricultural land for food in every village in Batu City, information obtained that there is significant effects of the percentage of farmers (X1), the land area for a decent life (X2), and the amount of food crops (X3) and the coefficient dependencies on lag (ρ) to the carrying capacity of farmland food (Y).